Investigation of Violations Committed by Armenia During the Karabakh Conflict Within the Framework of International Humanitarian Law Norms - Azoteyine, Sally Lariba; Aghayeva, Zarkhanim; Gasimov, Emil (ADA University, 2024)
The Karabakh region has been characterized by recurring armed battles and shaky ceasefires, deriving from Armenia's territorial claims over Azerbaijan, resulting in losses on both sides. Significant property devastation and human relocation have also resulted from the violence. This research highlights the insufficient examination of violations attributed to Armenia, despite accusations of violations of humanitarian law against both parties. Such military confrontations are detrimental to the advancement of sociopolitical development, particularly in areas of ethnic diversity such as Nagorno-Karabakh where respect for human rights is important. The purpose of this capstone project is to examine how little international humanitarian law has been done to look into Armenian transgressions. The study will employ qualitative approaches, including in-depth interviews with specific specialists in Azerbaijan, and make use of both primary and secondary data sources. With an emphasis on the opinions of attorneys and specialists in security and international humanitarian law, these interviews will collect descriptive data to comprehend the shortcomings of the investigations into Armenia's activities during the Karabakh conflict.
Keywords: Human rights -- Azerbaijan -- Case studies; Azerbaijan -- Foreign relations -- Armenia; International law -- Azerbaijan; Karabakh (Azerbaijan) -- History -- 21st century; Armed conflicts -- Social aspects -- Caucasus, South; Public and International Affairs